67.4k views
1 vote
6 + 18r = 20r - 18 - 4r

2 Answers

7 votes
6+18r=20r-18-4r
6+18r=18r-18
-6. -6
18r=18r-24
-18r. -18r
R=-24
User Mario Duarte
by
5.3k points
4 votes

Answer:

r = -12

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define

6 + 18r = 20r - 18 - 4r

Step 2: Solve for r

  1. Combine like terms: 18r + 6 = 16r - 18
  2. Subtract 16r on both sides: 2r + 6 = -18
  3. Isolate r term: 2r = -24
  4. Isolate r: r = -12
User Martincho
by
5.0k points